There’s No Such Thing as a Computer-Authored Work–And It’s a Good Thing, Too - Grimmelman, James (The Columbia Journal of Law & the Arts, 2016)
I would like to talk about computer-authored works—I would like to, except that they don’t exist. Copyright law doesn’t recognize computer programs as authors, and it shouldn’t. Some day it might make sense to, but if that day ever comes, copyright will be the least of our concerns. Instead, I will say something about why computer authorship is such a “bad penny of a question,” to use Annemarie Bridy’s felicitous phrase, even though it is so utterly speculative. The scholarship pondering the possibility of computerauthored works is surprisingly extensive, even though no one has ever exhibited even one work that could plausibly claim to have a computer for an “author” in the sense that the Copyright Act uses the term.